Kyrgyz Republic : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility-Staff Report; and Press Release on the Executive Board Consideration. (IMF Staff Country Reports; Country Report ;, 2006)
Economic activity in the Kyrgyz Republic has been buffeted by the political upheaval, and output growth has fallen short of expectations. The program builds on the country's entrenched fiscal prudence and features a tightening in monetary policy, so as to secure rapid sustained growth in a low-inflation environment. Structural reforms under the program will focus on financial sector development, public financial management, further measures to reduce the energy sector's quasifiscal losses, and improvements in the business climate. The main immediate risks to the outlook come from political pressures.